Financing Public Universities - Herbst, Marcel. author. aut Link
XVIII, 236 p.
Keywords: "Financing Public Universities" addresses newer practices of resource allocation which tie funding to indicators of performance. The gist of these efforts is to raise the quality of institutional systems. Performance-based budgeting and funding of public universities is part of broader efforts to reform public management, and it is being promoted and implemented by various government agencies around the globe. In particular, European universities with their normally strong governmental ties, or higher education systems molded on European universities, are prime targets of such reforms. Performance funding has made its inroads in attempts to grant university systems managerial autonomy: autonomy was to be granted in exchange for funding modes which are tied to the measurement of performance indicators. Unfortunately, performance-based budgeting or funding measures cannot meet the various expectations: they do not raise the quality of teaching or learning; they do not raise research performance; they take back a great deal of managerial autonomy which is commonly judged to be essential for the well being of higher education institutions, in particular research universities; and they act as automata in place of proper governance and management. "Financing Public Universities" addresses policy makers, higher education administrators, scholars and students of higher education management. After an introduction to the theme and to the book (Chapter 1), "Financing Public Universities" covers the evolvement of mass higher education and the associated curtailment of funding (Chapter 2), the public management reform debate (Chapter 3) within which performance-based budgeting or funding evolved (Chapter 4), sketches alternative governance and management modes which can be used instead (Chapter 5), and epitomizes inertia or challenges (Chapter 6). Four appendices cover more technical matters, such as a comparative exposition of the research performance of universities by nation (Appendix C) and examples of funding systems in the UK and in the USA (Appendix D). The author of this book is a former university administrator who finally became a researcher. This unusual background provides the author with a special understanding of university management but also, as a privileged observer, with a profound insight on university life. (.......) This book is a basic tool for understanding universities in a period of reforms and transformations. Jose-Gines Mora, Technical University of Valencia, President of the EAIR The present compendium by Marcel Herbst is of great help for all those who are involved in reflecting about and shaping the future of higher education and research. The reader will find an abundance of information and many comparisons of existing systems as well as suggestions for future developments. The author offers the reader not only a description of the actual situation. The reader will also find a wealth of challenging personal views which may help his of her own process of reflection. Jakob Nuesch, President emeritus, Swiss Federal Institute of Technology in Zurich (ETH Zurich).